MUSCLE LATENCIES IN HEALTHY AND FUNCTIONALLY UNSTABLE PARTICIPANTS FOLLOWING A SIMULATED ANKLE SPRAIN. Issue 7 (11th March 2014) - Gautrey, C; Watson, T; Mitchell, A
Abstract : Background: Functional ankle instability (FAI) is a common pathology in sport which exhibits debilitating residual symptoms. In relation to FAI, many studies have investigated muscle latencies of the peroneus longus and tibialis anterior muscles; however, there is limited research on the gluteus medius muscle which provides stability in the frontal plane. Weakness in the gluteus medius may produce deviations in joint motion, a subsequent loss of stability and may contribute towards a repeated injury at the ankle. Objective: To determine whether FAI participants suffer from a neuromuscular deficit compared to healthy controls, as measured by muscle latency following a simulated ankle sprain mechanism. Design: Cross-sectional study. Setting: University biomechanics laboratory. Participants played at a semi-professional level of soccer. Participants: A convenience sample was used to recruit twenty males with unilateral FAI and twenty male healthy controls. Inclusion criteria included males, aged 18–25 years, who participated in semi-professional soccer and who were right leg dominant. Intervention: Three perturbations on a standing tilt platform simulating the mechanics of an inversion and plantar-flexion ankle sprain. Subject group was the independent variable. Main outcome measure: Muscle latency in milliseconds of the peroneus longus, tibialis anterior and gluteus medius to the tilt platform perturbation. Results: The results indicated that there was a significant (P<.0125) delay in muscle latency of the peroneus longus, tibialis anterior and gluteus medius when comparing the unstable and stable ankle of the FAI group to the dominant and non-dominant ankle of the healthy group. Conclusion: Muscle latency was delayed in both the unstable and stable ankle of the FAI participants, which would suggest a central mechanism of control, or possibly a genetic predisposition to FAI. Rehabilitation prescribed by sports clinicians should focus on both limbs in functionally unstable individuals, as well as more proximal musculature such as the gluteus medius.